Statistics data analysis on specialized neurosurgical care giving in cerebrovascular diseases in Ukraine - Sapon, N. A.; Nikiforova, A. N.; Chitaeva, G. E.; Kyrychenko, V. M. (Ukrainian Neurosurgical Journal, 2010)
On basis of statistics data about treatment activity of neurosurgical departments in Ukraine in period from 1997 to 2998 years the analysis of neurosurgical care giving to patients with cerebrovascular diseases (CVD) was made. The amount of patients with CVD been treated at neurosurgical departments of Ukraine in 2008 increased in 2 times compared with 1997 — from 3350 to 7160. Surgical activity increased on 8.8% (from 27.1 to 35.9%), thus absolute index of operations quantity increased in 2.7 times — from 963 in 1997 to 2573 in 2008. Common lethality at these 12 years have been analyzed, was not considerably variable, it was in scope (10.8±0.55)% (p<0.05). As about postoperative lethality, after it’s index considerable growing in 1998 (from 17 to 21.9%), it diminished gradually and in 2008 became 17% (that is level of 1997). Surgical activity considerable increasing at patients with CVD at permanent indexes of common and postoperative lethality was conditioned by improvement of organization of specialized neurosurgical care giving, neurovascular departments establishing and highly qualified specialists of neurovascular field training.